2017
DOI: 10.1021/acsenergylett.7b00047
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Carbon Dioxide to Methanol in the Presence of Benzannulated Dihydropyridine Additives

Abstract: Dihydropyridines (DHPs) have been postulated as active intermediates in the pyridine-mediated electrochemical conversion of CO2 to methanol, however the ability of isolated DHPs to facilitate methanol production in a similar fashion to their parent aromatic N-heterocycles (ANHs) has not been tested. Here, we use bulk electrolysis to show that 1,2-and 1,4-DHPs (1,2-dihydrophenanthridine and 9,10dihydroacridine) can mediate the sub-stoichiometric electrochemical reduction of CO2 to methanol and formate with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 48 publications
(142 reference statements)
2
48
0
Order By: Relevance
“…Several adsorptionf ree energy studies found that Py and DHP favorably bind to the GaP surface, whereas CO 2 does not. [21] These studies suggest that hydrogenated N-heterocycles (HNHs)c an form on electrode surfaces under electrochemical conditions, and that such HNHsm ight be responsible for the heterogeneousr eduction of CO 2 . SCE computed for the solvated GaP(110) surface and À1.68 Vv s. SCE computed for the solvated reconstructed GaP(111)s urface).…”
Section: Introductionmentioning
confidence: 99%
“…Several adsorptionf ree energy studies found that Py and DHP favorably bind to the GaP surface, whereas CO 2 does not. [21] These studies suggest that hydrogenated N-heterocycles (HNHs)c an form on electrode surfaces under electrochemical conditions, and that such HNHsm ight be responsible for the heterogeneousr eduction of CO 2 . SCE computed for the solvated GaP(110) surface and À1.68 Vv s. SCE computed for the solvated reconstructed GaP(111)s urface).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Thev arying composition in Pd x Cu y aerogels resulted in different Pd 0 /Pd II and Cu I + Cu 0 /Cu II radios,w hich was found to be correlated with the CO 2 electrocatalytic activity and CH 3 OH selectivity.M oreover, the special nanochain structure of aerogels also contributed to the enhancement of Pd/Cu grain boundaries and CH 3 OH production. We prepared as erious of Pd x Cu y bimetallic aerogels with controlled composition via at emplate-free self-assembly process.B y using Pd 83 Cu 17 bimetallic aerogels on carbon paper (CP) as electrode and 1-butyl-3-methylimidazoliumtetrafluoroborate ([Bmim]BF 4 )a queous solution as electrolyte,t he Faradaic efficiency for CH 3 OH production could reach 80.0 %w ith acurrent density of 31.8 mA cm À2 ,which is higher than those reported previously.…”
mentioning
confidence: 99%
“…We prepared as erious of Pd x Cu y bimetallic aerogels with controlled composition via at emplate-free self-assembly process.B y using Pd 83 Cu 17 bimetallic aerogels on carbon paper (CP) as electrode and 1-butyl-3-methylimidazoliumtetrafluoroborate ([Bmim]BF 4 )a queous solution as electrolyte,t he Faradaic efficiency for CH 3 OH production could reach 80.0 %w ith acurrent density of 31.8 mA cm À2 ,which is higher than those reported previously. [25][26][27][28] Thev arying composition in Pd x Cu y aerogels resulted in different Pd 0 /Pd II and Cu I + Cu 0 /Cu II radios,w hich was found to be correlated with the CO 2 electrocatalytic activity and CH 3 OH selectivity.M oreover, the special nanochain structure of aerogels also contributed to the enhancement of Pd/Cu grain boundaries and CH 3 OH production.…”
mentioning
confidence: 99%